Systemic violence in drug markets - Reuter, Peter (Crime, law and social change, 2009)
Even without the protection of the state and courts, illegal drug markets are generally peaceable. However occasionally specific markets exhibit high levels of violence. This essay examines the sources that might generate such violence, some internal to organizations (successional and disciplinary), some between organizations (territorial or transactional) and others between drug dealers and the state or its representatives. Particular attention is given to the extremely high rates of killing in the high level Mexican drug markets in 2007-2008 and what motivates the variety of targeted victims, including innocent parties and corrupt officials. The other episode examined in detail is the US crack market in the 1980s. The emphasis here is on the youth of the participants, the value of the drug itself and the intensity of law enforcement.